Synthesis of a rigid C3v-symmetric tris-salicylaldehyde as a precursor for a highly porous molecular cube - Elbert, Sven; Rominger, Frank; Mastalerz, Michael (Chemistry - a European journal, 2014)
The development of a synthetic approach to a C3v-symmetric tris-salicylaldehyde based on triptycene is presented. The tris-salicylaldehyde is a versatile precursor for porous molecular materials, as demonstrated in the [4+4] condensation reaction with a triptycene triamine to form a molecular shape-persistent porous cube. The amorphous material of the molecular porous cube shows a very high surface area of 1014 m2 g−1 (BET model) and a high uptake of CO2 (18.2 wt % at 273 K and 1 bar). Furthermore, during the multistep synthesis of the tris-salicylaldehyde precursor, a relatively rare (twofold) addition of the aryne to the anthracene in the 1,4- and 1,4,5,8-positions have been found during a Diels-Alder reaction, as proven by X-ray structure analysis.
Gesehen am 16.10.2020
Im Titel ist der Ausdruck "3v" tiefgestellt